2019
DOI: 10.3389/fmicb.2018.03288
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity of the Dickeya Bacteriophage PP35 Is Directed by a Tail Spike Interaction With Bacterial O-Antigen, Enabling the Infection of Alternative Non-pathogenic Bacterial Host

Abstract: Dickeya solani is a recently emerged virulent bacterial potato pathogen that poses a major threat to world agriculture. Because of increasing antibiotic resistance and growing limitations in antibiotic use, alternative antibacterials such as bacteriophages are being developed. Myoviridae bacteriophages recently re-ranked as a separate Ackermannviridae family, such as phage PP35 described in this work, are the attractive candidates for this bacterial biocontrol. PP35 has a very specific host range due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Many bacteriophages use tail spike/fiber proteins for primary contact with bacterial surface polysaccharides. A recognition mechanism involving lipopolysaccharides (LPS) and capsule polysaccharides was suggested as common for SPR phages (Evans et al, 2010) and was experimentally shown for Dickeya phage PP35 (Kabanova et al, 2019) and Pectobacterium carotovorum subsp. carotovorum phage POP72 (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many bacteriophages use tail spike/fiber proteins for primary contact with bacterial surface polysaccharides. A recognition mechanism involving lipopolysaccharides (LPS) and capsule polysaccharides was suggested as common for SPR phages (Evans et al, 2010) and was experimentally shown for Dickeya phage PP35 (Kabanova et al, 2019) and Pectobacterium carotovorum subsp. carotovorum phage POP72 (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many Podoviridae phages tend to interact with bacterial polysaccharides (lipopolysaccharides, sugar moieties of the O-antigen or capsule polysaccharides) as primary receptors for host recognition [42]. Several phages infecting SRP have been experimentally shown to follow this rule [16,[43][44][45]. Despite the diversity of species and strains comprising SRP, very limited information is available on both the composition of polysaccharides of Pectobacterium and Dickeya, and the details of phage interaction with the polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Only eight structures of polysaccharides of P. atrosepticum [36,46,47], P. wasabiae [48], P. carotovorum (then Erwinia carotovora subsp. carotovora) [49], P. brasilense [45] and D. solani [44,50] have been identified. Thus, the research on pectobacterial polysaccharide is important for the development of phage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For detailed examination of phage-encoded polysaccharide depolymerases that bind and degrade bacterial glycans see Latka et al (43). Given the potential for broad host range depolymerases uncoupled from phages, these enzymes are being explored as therapeutic antibacterials against encapsulated bacterial pathogens (44)(45)(46)(47).…”
Section: Polysaccharidesmentioning
confidence: 99%